2014
DOI: 10.6023/cjoc201403022
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Pyrrolo[1,2-a]quinoxaline Derivatives through Copper-Catalyzed Cascade Reactions

Abstract: A simple, efficient, inexpensive one-pot method for the pyrrolo[1,2-a]quinoxaline derivatives synthesized from 2-formylazoles and o-aminoiodoarenes was developed by using cheap CuI as catalyst, inexpensive and readily available 2,2'-bipyridine as ligand at 110 ℃. The reaction provides an efficient protocol to a series of pyrrolo[1,2-a]quinoxaline derivatives in good to high yields, and benefits of readily available catalyst and synthesis of high efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Organic corrosion inhibition is the most effective and flexible means of protecting the severe internal corrosion of carbon steel pipelines in oil product transportation (Xiao et al, 2008;Xu et al, 2013;Qin et al, 2010;Dong et al, 2011). Since it was found that imidazoline based on inhibitors has a highly inhibition ability in acidic media, it is widely used to minimize carbon dioxide-induced corrosion in the oil and gas industry (Jiang et al, 2014). But the imidazoline ring structure is thermally unstable at high temperature (Ke et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Organic corrosion inhibition is the most effective and flexible means of protecting the severe internal corrosion of carbon steel pipelines in oil product transportation (Xiao et al, 2008;Xu et al, 2013;Qin et al, 2010;Dong et al, 2011). Since it was found that imidazoline based on inhibitors has a highly inhibition ability in acidic media, it is widely used to minimize carbon dioxide-induced corrosion in the oil and gas industry (Jiang et al, 2014). But the imidazoline ring structure is thermally unstable at high temperature (Ke et al, 2014).…”
Section: Introductionmentioning
confidence: 99%